2018
DOI: 10.30699/acadpub.ijbd.11.2.16
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Relationship Between Epstein - Barr virus and Breast Cancer in Isfahan Province

Abstract: Introduction:Breast cancer is one of the most common malignancies in women. Although the etiology of breast carcinoma is not completely understood, exposure to Epstein-Barr virus (EBV) is suggested as a risk factor for breast cancer. Studies have reported since 1995 that EBV is involved in the development of breast cancer. The aim of this study was to assess the presence of EBV in patients with breast cancer in Isfahan province. Methods:This study was performed using 40 paraffin-embedded tumor tissues and 40 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…showed that from 40 cancerous breast tissues, 20 of them (50 %) and from 40 healthy samples, under study five of them (12.5 %) were positive [148], Richardson et al showed that 24 (34 %) of tumour samples and nine (13 %) control samples were EBV positive. They used QPCR technique on 70 tumour and control samples [149].…”
Section: Epstein-barr Virus (Ebv) and Breast Cancermentioning
confidence: 95%
See 1 more Smart Citation
“…showed that from 40 cancerous breast tissues, 20 of them (50 %) and from 40 healthy samples, under study five of them (12.5 %) were positive [148], Richardson et al showed that 24 (34 %) of tumour samples and nine (13 %) control samples were EBV positive. They used QPCR technique on 70 tumour and control samples [149].…”
Section: Epstein-barr Virus (Ebv) and Breast Cancermentioning
confidence: 95%
“…Analysis of genomic DNA from cancerous samples using EBV specific primers done by Salahshournia et al . showed that from 40 cancerous breast tissues, 20 of them (50 %) and from 40 healthy samples, under study five of them (12.5 %) were positive [ 148 ], Richardson et al . showed that 24 (34 %) of tumour samples and nine (13 %) control samples were EBV positive.…”
Section: Introductionmentioning
confidence: 99%